Integrating Soft Skills into Ayurveda Graduates: A Contemporary Imperative - Soni, Gaurav; Neelam (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: The Bachelor of Ayurvedic Medicine and Surgery (BAMS) curriculum immerses students in Ayurvedic principles, transforming them into stewards of this ancient therapeutic system. Upon graduation, practitioners frequently engage in public healthcare environments, where they encounter problems such as patient animosity, unprofessional conduct, and emotionally sensitive situations. BAMS graduates possess expertise in Ayurvedic principles; yet the lack of structured soft skills training leads to heightened stress and anxiety in their professional endeavors. Materials and Methods: This review study investigates the significance of soft skills – namely effective communication, empathy, adaptability, and teamwork – in improving the professional preparedness of BAMS graduate. Innovative pedagogical tools, such as interactive training modules, role-playing situations, and mindfulness practices, are suggested for incorporation into the curriculum. Results: Incorporating specialized soft skills training in the BAMS program provides practitioners with the necessary tools to manage difficult situations, establish patient trust, and cultivate collaborative professional relationships. These interventions equip graduates to handle stress competently, adapt to evolving situations, and deliver comprehensive, patient-centered care. Discussion: Soft skills are essential for BAMS practitioners operating in varied and challenging public healthcare environments. By incorporating the curriculum to incorporate systematic soft skills training, Ayurveda education can cultivate well-rounded professionals who resonate with the tradition’s holistic principles. Subsequent study ought to assess the effects of these curriculum modifications on practitioner well-being and patient satisfaction. Conclusion: By recognizing the importance of soft skills and incorporating focused tactics into the curriculum, educational institutions can enable BAMS students to adeptly navigate the intricacies of healthcare with empathy and professionalism.